Leibniz and the First Law of Thermodynamics - Lochmanová, Kateřina (Teorie vědy / Theory of Science, 2024)
The article presents the German philosopher G. W. Leibniz as a key precursor of the First Law of Thermodynamics. In this way, Leibniz tried to oppose Newton, who seems to have completely rejected the First Law of Thermodynamics, while at the same time remarkably anticipating the Second. Based on his polemics not only with Newton, from whose Laws of Motion thermodynamics originates, and with his advocate Samuel Clarke, but also with René Descartes, whose conception Leibniz partially followed, Leibnizʼs reasoning turns out to be the most convincing. It is certainly no coincidence that the later founders of thermodynamics frequently acknowledged him.